IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF SENI BUDAYA KELAS VII DI SMP N 8 BATAM NONGSA BERBASIS ANDROID MENGGUNAKAN ADOBE ANIMATE - AZRIANI, ERA; Fauzi, Rahmat (LPPM Universitas Putera Batam, 2023)
This study aims to produce learning media in the form of android-based applications for junior high school students. Based on research on student learning outcomes at SMPN 8 BATAM in the subject of Cultural Arts, it is a subject that has a low score compared to other subjects, namely 71. This is shown by data from 39 students, there are 24 students (61.53%) who get a score below the Minimum Completeness Criteria (KKM), which is 68, while the remaining 15 students (38.67%) score above the KKM. In this way, the researcher is interested in designing an Android-based Interactive Learning Media for Cultural Arts Class VII application using Adobe Animate. This prompted the author to build a multimedia-based application using the waterfall method. The conclusion obtained in this study is that interactive art and culture learning media applications can be used as additional learning media that are interesting and not boring.